COMPARATIVE STUDY OF YOGIC PRACTICES AT YOGA INSTITUTE AND YOGA STUDIOS - Naseev Kumar; Kapruwan, Vijendra Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to find out the changing perspectives-practices-understanding of Yoga in the olden era and in the modern era. Yoga has become popular and commercialized so authentic practices of yoga become very much modified. Many yoga teachers have a wrong understanding about the concept of Yoga. The purpose of the study, 10 yoga institutes and studios of Pune city were randomly selected for observation. Their style of teaching Yoga and methods of classes. After observing 5 yoga institutes and studios respectively, it was observed that the many Yoga institutes teach traditional style of Yoga but Yoga studios teach modification in Yoga classes. Traditional way of practicing yoga is for example – Raja Yoga/Patanjal Yoga, Karma Yoga, Ashtanga Yoga, Hatha Yoga, Jnyana Yoga, Nath Yoga, Bhakti Yoga, Mantra Yoga, Laya Yoga etc. and modern way of practicing Yoga - Hot yoga, Power yoga, Beer yoga, Wine yoga etc. so the real purpose of yoga is not fulfilled here by Yoga studios. There is a need to increase more awareness about traditional yoga. The experimental results show that the traditional methods are correct by giving them the right material of yoga and to make Yoga as a lifestyle.